(untitled) (Vietnam Journal of Community Medicine, 2026)
Objective: To determine the prevalence of stroke associated pneumonia in ischemic stroke patients and related factors at the Department of Neurology, Cho Ray Hospital. Subjects and methods: A retrospective cohort study was conducted on 242 ischemic stroke patients admitted to the Department of Neurology from December 2023 to June 2025. Data on demographics, clinical, and outcome data were collected. Firth logistic regression with LASSO selection was used to identify independent predictors. Results: The prevalence of stroke associated pneumonia was 16.53%. Compared to the non-stroke associated pneumonia group, the stroke associated pneumonia group had significantly worse clinical outcomes, including a higher rate of poor outcomes (mRS ≥ 3) (80% vs. 36.7%; p < 0.001) and a longer mean hospital stay (5.43 vs. 3.87 days; p < 0.001). The optimal LASSO model identified three robust independent predictors for stroke associated pneumonia: dysphagia (OR = 6.81; p = 0.001), aphasia (OR = 3.71; p = 0.022), and baseline NIHSS score (OR = 1.15; p = 0.007). Conclusion: The prevalence of stroke associated pneumonia in ischemic stroke patients at Cho Ray Hospital is quite high, and is associated with poor outcomes. Dysphagia, aphasia, and stroke severity (NIHSS score) are important independent predictors, helping to identify high-risk patients early.